Pore structure of different macroscopically distinguished components within low-rank coals and its methane desorption characteristics. (1st June 2021) - Zheng, Chao; Ma, Dongmin; Chen, Yue; Gao, Zheng; Teng, Jinxiang
Highlights: The micropores of vitrain are more developed than those of durain. The connectivity between and within different type pores in durain is better than that of vitrain. The adsorption capacity of vitrain is lower than that of durain. The desorption ratio of durain is higher than that of vitrain. The water plays a positive role in the process of methane desorption. Abstract: The pore structure of the macroscopically distinguished components is complex, which directly affected methane adsorption/desorption. In this paper, mercury intrusion porosimetry (MIP), liquid nitrogen adsorption (LNA), scanning electron microscope (SEM), nuclear magnetic resonance (NMR) were used to describe the pore structure of vitrain and durain within low-rank coals. The results indicate that pores mainly were classified as micropores and transition pores, in which micropores are dominant, and transition pores in durain are more developed than vitrain. The total specific surface area of durain is 1.13 times that of vitrain, but the BET specific surface area of vitrain is 1.32 times that of durain. Comparison of T2 spectra between saturation and centrifugation, the connectivity between and within different types of pores in durain is better than that of vitrain. The adsorption capacity of durain is higher than that of vitrain. The contribution of specific surface area (SSA) to methane adsorption is less than pore connectivity. The desorption ratio of durain is higher than that of vitrain, it can be considered that pore connectivity is the key factor to control the methane adsorption/desorption performance of different macroscopically distinguished components. The desorption ratio of the moisture equilibrium sample is relatively higher than that of the air-dried based sample, the isosteric adsorption heat of air-dried based sample is higher than that of the moisture equilibrium sample, showing that water plays a positive role in the process of methane desorption. The interface between vitrain and durain is the high-frequency position of methane production.